co227_a2 - + x 4 = 2 4 x 1 + x 2-3 x 3 + 4 x 4 = 1 2 x 1 +...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Assignment 2 Due: Wednesday October 12 at the BEGINNING of class 1. Convert the following linear programs into standard equality form: (a) minimize x 1 - 6 x 2 + 4 x 3 subject to 8 x 2 + x 3 5 x 1 - 8 x 2 0 x 2 0 (b) maximize 5 x 1 + 2 x 2 - x 3 subject to - 5 x 1 + 3 x 2 + x 3 = - 2 x 1 + x 2 - 3 x 3 7 2 x 1 + x 3 2 x 1 0 2. Write a linear program in standard equality form that satisfies the following: (a) A linear program with one variable that is unbounded. (b) A linear program with one variable that is infeasible. (c) A linear program with one variable that has an optimal solution. 3. Given the following linear program, prove whether the linear program is infeasible, unbounded, or has an optimal solution with an appropriate certificate and show the validity of the certificate. You may use any of the given vectors in your analysis. (a) maximize x 1 - x 2 + x 3 subject to 2 x 1 - x 2 + x 3 = 2 - x 1 + 2 x 2 - 5 x 3 = 2 4 x 1 - x 2 - x 3 = 6 x 1 ,x 2 ,x 3 0 r = (1 , 3 , 1) T , x = (2 , 2 , 0) T , y = ( - 2 , - 1 , 1) T (b) maximize x 1 + x 2 + 2 x 3 - x 4 subject to 3 x 1 + 5 x 2 + 6 x 3
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: + x 4 = 2 4 x 1 + x 2-3 x 3 + 4 x 4 = 1 2 x 1 + 3 x 2-2 x 3 = 5 x 1 ,x 2 ,x 3 ,x 4 r = (1 , 2 , 3 , 4) T , x = (2 , 1 , ,-1) T , y = (1 , 2 ,-1) T (c) maximize 2 x 1 + x 2 + 4 x 3 subject to 2 x 1-x 2 + x 3 = 2-x 1 + 2 x 2-5 x 3 = 2 4 x 1-x 2-x 3 = 6 x 1 ,x 2 ,x 3 r = (1 , 3 , 1) T , x = (2 , 2 , 0) T , y = (-2 ,-1 , 1) T 4. For the following, choose a basis, nd the corresponding basic solution and improve the solution. (a) maximize x 1-x 3 + 4 x 5 subject to 3 x 1 + 5 x 3 + x 4-x 5 = 3-x 1 + x 3-2 x 5 + x 6 = 2 x 1 + x 2 + 2 x 3 + 3 x 5 = 3 x 1 ,x 2 ,x 3 ,x 4 ,x 5 ,x 6 (b) maximize-x 1 + 2 x 3 + 4 x 6 subject to x 1 + 4 x 3 + x 5 + x 6 = 4 x 2-x 3 + 3 x 6 = 2 2 x 3 + x 4-2 x 6 = 1 x 1 ,x 2 ,x 3 ,x 4 ,x 5 ,x 6...
View Full Document

This note was uploaded on 11/15/2011 for the course CO 227 taught by Professor 1 during the Fall '10 term at Waterloo.

Page1 / 2

co227_a2 - + x 4 = 2 4 x 1 + x 2-3 x 3 + 4 x 4 = 1 2 x 1 +...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online